Application of dual membrane technology for municipal wastewater reuse - Iong, Kiong Yew. (2008)
Due to the increase in Singapore’s population and industrialization, the demand of water is increasing each year. With growing pressure to locate new freshwater resources, wastewater reuse is now a viable alternative source of water. Different technologies have been used to reclaim municipal wastewater for industrial reuse and Membrane Technology has been the fore-runner in such application. With recent improvements in membrane technology, especially in microfiltration, ultrafiltration and reverse osmosis, membrane technology is now able to reclaim municipal wastewater for reuse.